2009
DOI: 10.1093/abbs/gmp016
|View full text |Cite
|
Sign up to set email alerts
|

The role of P2X7 receptor in ATP-mediated human leukemia cell death: calcium influx-independent

Abstract: Activation of the P2X7 receptor leads to a rapid, bidirectional flux of cations, causing broad range of biological responses including cytotoxicity. However, the mechanism of P2X7-mediated cytotoxicity remains largely unexplored. In our previous study, the lack of P2X7-mediated calcium response under normal conditions was found in P2X7(+) hematopoietic cell lines. In this study, the P2X7-mediated cytotoxicity in different type of cells (P2X7(-), P2X7(+) with calcium response, and P2X7(+) without calcium respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…P2X7 receptor expression was significantly higher (relative to bone marrow mononuclear cells) in cells from patients with lymphoblastic leukaemia (as well as acute and chronic myelogenous leukaemia) [467]. It has been claimed that the P2X7 receptor-mediated cytotoxic effects on KGla and J6-1 leukaemia cell lines may occur independently of the calcium response [468]. In paediatric acute leukaemia, RT-PCR and Western blots showed that P2X1, P2X4, P2X5 and P2X7 receptors were upregulated, while P2X2, P2X3 and P2X6 receptors were absent or marginally expressed and the highest expression of P2X7 receptors was found in relapsed patients [469].…”
Section: Lymphocytic Leukaemiamentioning
confidence: 99%
“…P2X7 receptor expression was significantly higher (relative to bone marrow mononuclear cells) in cells from patients with lymphoblastic leukaemia (as well as acute and chronic myelogenous leukaemia) [467]. It has been claimed that the P2X7 receptor-mediated cytotoxic effects on KGla and J6-1 leukaemia cell lines may occur independently of the calcium response [468]. In paediatric acute leukaemia, RT-PCR and Western blots showed that P2X1, P2X4, P2X5 and P2X7 receptors were upregulated, while P2X2, P2X3 and P2X6 receptors were absent or marginally expressed and the highest expression of P2X7 receptors was found in relapsed patients [469].…”
Section: Lymphocytic Leukaemiamentioning
confidence: 99%
“…P 2X receptors exert widespread physiological roles in tissues such as the adult and developing nervous system, the respiratory, gastrointestinal, cardiovascular and genitourinary systems [45]. Abnormally high expression of P 2X7 was observed in solid tumors [46,47], as well as in hematologic malignancies, such as B-cell CLL [48], acute leukemia and myelodisplastic syndromes [49,50]. Moreover, a series of P 2X7 polymorphisms have been discovered, whose impact on P 2X7 functions, mechanisms and relationship with diseases were studied in a number of variants.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…MRS1754 has reinforced the important role of adenosine in suppressing the inflammatory response and has indicated that A 2B receptors are essential in these anti-inflammatory actions [52,65]. As with many other A 2B receptor antagonists, MRS1754 has again reinforced the suggestion that targeting the A 2B receptor may prove therapeutically useful [23].…”
Section: Asc-397-mrs 1754mentioning
confidence: 97%
“…In addition to having been implicated in areas such as pain and neurological diseases, the P2X 7 receptor has also been shown to be essential in other physiological areas and has notably been associated with cell proliferation and apoptosis [52]. KN-62, in addition to being a reversible and selective inhibitor of Cam Kinase II, is a potent, noncompetitive antagonist at the P2X 7 receptor (IC 50 value= 25 nM) [14].…”
Section: Asc-421-kn-62mentioning
confidence: 99%
See 1 more Smart Citation